2013
DOI: 10.4103/2278-9626.115992
|View full text |Cite
|
Sign up to set email alerts
|

A simplified model for biomedical waste management in dental practices - A pilot project at Thane, India

Abstract: A lot of biomedical waste (BMW) is generated in dental practices, which can be hazardous to the environment as well as to those who come in contact with the materials, if not dealt with appropriately. Most of the rules world-wide are not specific for dental BMW management and hinder easy understanding by dental practitioners. Because of lack of clear-cut guidelines either from Dental Council of India or Government of India or Indian Dental Association (IDA) on disposal of dental wastes, this article is designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…[1] According to the WHO fact sheet, approximately 20% of waste generated by various health care units is reported to be hazardous. [7] Rapid urbanization and population growth has led to more and more number of hospitals and private clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] According to the WHO fact sheet, approximately 20% of waste generated by various health care units is reported to be hazardous. [7] Rapid urbanization and population growth has led to more and more number of hospitals and private clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Biomedical waste is generated in hospitals, nursing homes, blood bank, and pathological laboratories during diagnosis, treatment, or immunization of various diseases. [1]…”
Section: Introductionmentioning
confidence: 99%
“…BMW management should be strictly implemented and monitored in a systematic and simplistic manner by authoritative bodies in India and other developing countries. The governmental bodies should take responsibility of making these services available to the practicing dentists as well as dental hospitals ( 19 ). The authors recommend similar studies in different states and further research to provide accurate data for future decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these sources, residential sources also contribute to environmental mercury which comes from human waste, laundry greywater, and certain consumer products The releases of mercury from dentistry has been receiving attention in recent years. Studies (Chin, 2000, Condrin et al, 2004 found that dentistry contributed only a small fraction -less than 1 % -to total mercury releases and recent studies (Baghele, 2013, more reference) estimate these releases at 3-4 %. In Oregon, the total this rate is about 1.5 % (DEQ, 2006).…”
Section: Sources and Levels Of Mercury In The Environmentmentioning
confidence: 99%